Teori Komunikasi:Kisah Pengalaman Amerika - Hardjana, AndrÃƒÂ© (FISIP Universitas Atma Jaya Yogyakarta, 2004)
Being an interdisciplinary science, communication ows its key concepts and theoreties to other scientific fields. The body of communication knowledge grew out of research works undertaken by those scholars who were actively involved in the various activities related to the war information management, some of whom were then pronounced Ã¢â‚¬Ëœfounding fathersÃ¢â‚¬â„¢ of communication research. This article briefly reviews the intensive interactions among those founding fathers during the war whose ideas were then drown together to constitute the communication field of study. Schramm was the institutionalizer of this new field of communication study. The development of communication theory now is largely depending on the various research works undertaken by those researchers Ã‚Â ffiliated with either the departments of communication or the schools of journalism mass communication in the US and Canada.